Implementation of 5P Marketing Strategy to Improve Non-BPJS Patient Loyalty at Surya Husada Primary Clinic, Indonesia - Azmi Fahrurrizal Amrulloh; Sentot Imam Suprapto; Yuly Peristiowati (Health and Technology Journal (HTechJ), 2025)
Patient loyalty is a critical determinant of sustainability for private healthcare providers, particularly in developing countries where competition with public insurance systems is intense. This study aimed to analyze the influence of the 5P marketing mix strategy—product, price, place, promotion, and people—on the loyalty of non-National Health Insurance (non-BPJS) patients at Klinik Pratama Surya Husada Tulungagung, Indonesia. A quantitative explanatory design was employed with a sample of 110 non-BPJS patients selected through purposive sampling. Data were collected using a validated questionnaire and analyzed through multiple regression. Classical assumption tests confirmed normality, absence of multicollinearity, homoscedasticity, and autocorrelation, validating the regression model. The results indicated that product (β = 0.601, p < 0.001), promotion (β = 0.080, p < 0.001), and people (β = 0.308, p < 0.001) had significant positive effects on patient loyalty. In contrast, price (β = −0.070, p < 0.001) and place (β = −0.079, p < 0.001) showed significant adverse effects. The simultaneous effect test revealed that all five variables significantly influenced loyalty (F = 2026.128, p < 0.001). The coefficient of determination (R² = 0.990; Adjusted R² = 0.989) demonstrated that the 5P marketing mix could explain 99% of the variance in patient loyalty. These findings underscore the critical role of service quality, human resources, and effective promotion in strengthening patient loyalty, while pricing and accessibility require careful strategic adjustments. The study contributes to healthcare marketing literature by validating the 5P framework in the Indonesian primary care context. It provides actionable insights for private clinics seeking to enhance competitiveness in a dual healthcare system.